Failure of systemic oral doxycycline in preventing ocular toxoplasmic retinochoroiditis in French military personnel. Issue 2 (8th January 2018) - Saad, Sami; Delbarre, M; Saad, R; Berguiga, M; Benisty, D; Marechal, M; Adam, T; Froussart, F
Abstract : This paper describes two cases of toxoplasmic chorioretinitis presenting in two French soldiers who had been receiving oral doxycycline for malaria prophylaxis. This is despite the proven effectiveness of oral doxycycline in treating Toxoplasma gondii, the most common cause of this infection. The lack of effectiveness of oral doxycycline in these two cases most likely reflected that the ocular concentration of 100 mg daily doxycycline is too low to treat or prevent Toxoplasmic retinochoroiditis (TC). Clinicians should therefore be aware that soldiers taking prophylactic oral doxycycline are still at risk of developing ocular TC with potentially sight-threatening consequences if not treated adequately.